Labour market institutions and the challenge of allocating the right people to the right jobs: Evidence on the relation between labour market institutions and optimal skill matching from 28 industrial countries. Issue 2 (17th February 2020) - Fregin, Marie-Christine; Levels, Mark; van der Velden, Rolf
ABSTRACT: This article provides empirical evidence on the relation between institutional characteristics of labour markets that frame allocation processes, and optimal skill matching at the individual level. We investigate the extent to which skill-based job-worker matches are associated with employment protection legislation (EPL), unemployment benefits, and enforcing and enabling activating labour market policies. Drawing on data of the OECD's Programme for the International Assessment of Adult Competencies (PIAAC), and performing cross-country analyses of 28 industrial countries, we find that EPL can explain variance in the share of optimal skill matching across countries, displaying a positive relation. We also find a negative relation between strict enforcing activating labour market policies and optimal skill matching.